The Effect of Welfare and Work Motivation on Employee Productivity at the Lampung Provincial Public Works Agency - Vinka Eriza Arliandri; Iskandar Ali Alam (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2026)
Employee productivity is a key factor in improving well-being and work motivation at the Lampung Provincial Public Works and Construction Agency. This study aims to analyze the influence of well-being and work motivation on employee productivity. A descriptive quantitative method was used, with a sample of 85 employees selected via Proportionate Stratified Random Sampling. Data were collected through the distribution of questionnaires to all employees. The collected data were analyzed using multiple linear regression. The results of this study indicate that employee well-being and work motivation have a significant effect on employee productivity. All variables were found to be valid and reliable.